The Characteristic of Mubdil in Hajj (Analisis of Fiqh Al-Hadith) - Yulia Rahmi; Norzulaili Mohd Ghazali (UIN K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper explores the issue of mubdil on Hajj Badal. A mubdil is a person who replaces the entire series of Hajj from Mubdal Minhu (a person being replaced). The narration of the hadith explains that a mubdil is a child or sibling of a person the person being replaced. In reality, many practices of hajj badal are carried out by people who do not have a descendant relationship with mubdal minhu, even the mubdil does not know the person he has replaced absolutely, and vice versa. there were also cases of misapplication of responsibility and fraud of hajj badal by replacing more than one mubdal minhu. The practice of hajj badal is based on the hadiths of Rasulullah which inform about replacing others in the Hajj because of physical conditions or because of death. The hadiths will be examined using the fiqh al-hadith method by studying the hadiths based on their relationship with the verses of the Qur'an and other hadith and through the textual and contextual approach of the hadith. Based on this method, it can be explored how the characteristics that must be possessed by a mubdil. The realization of these characteristics can minimize the occurrence of misuse of responsibility and trust in Hajj Badal.